Pengaruh Pendidikan Kesehatan Menggunakan Modul Menarche Terhadap Tingkat Pengetahuan Tentang Menstruasi Terhadap Siswa Kelas IV-V Di SDN Gedongkiwo Yogyakarta - Zasti Ruwihapsari; Maryana Maryana (Poltekkes Kemenkes Yogyakarta, 2018)
School-age children are transition period into early adolescence. This school-age children period begins with coming into to school environment, which has a significant impact on children's development and relationships with others. In this transition, it must be children adjustment in touch with others and also a process of physical and sexual maturation. One sign of sexual maturity in a young girl is experiencing a menstrual period. Based on the early survey were obtained from 10 students in class IV-V SDN Gedongkiwo Yogyakarta that 6 of them do not understand about menstruation, it is shown by their confused and feelings of anxiety and fear of first menstruation when asked. This suggests that health information is needed to be given to young girl students so that they can face and prepare for and give respond to menarche happening to them. Purpose: The purpose of this research is to know the influence of health education using Menarche Module towards the level of knowledge about menstruation on girl students class IV-V in SDN GedongkiwoYogyakarta 2013. Method: The research conducted in this study uses Quasi-experiments “pre-test post-test with control design”. The populations in this study were all girl students in class IV-V SDN Gedongkiwo Yogyakarta. The researcher uses the total sampling technique that divided into 2 groups: a control group and a treatment group with inclusion and exclusion criteria, so the total samples in this study as many as 53 people. Result: The result showed there are influences of health education using Menarche Modules towards the level of knowledge about menstruation on girls students class IV-V in SDN Gedongkiwo Yogyakarta. This is indicated by the value of t account is greater than t table about 3.519>2.000 or p = 0.001 (p < 0.05).